Crack initiation and propagation in pre-cracked rock specimens - Cai, Xiao (2015)
This report sums up the results of an investigation on the influence of flaw inclination and width of specimens on crack initiation and propagation for molded gypsum specimens under compression. Molded gypsum specimens without flaw (as reference), and with 1.3mm wide flaws of inclinations 0° 15°, 30°,and 90° were tested. Uniaxial compression was conducted using INSTRON Uniaxial Compression Machine, and a PHANTOM v310 high speed camera was used to record high-speed video for conducting crack analysis afterwards. Total of 87 specimens were tested, and 38 crack analysis were done and combined for investigation. The cracking process were traced and initiation and propagation sequence were re-constructed by playing the high speed video. Data for crack initiation strain, crack initiation stress, failure strain and failure stress for each specimen analyzed were extracted and consolidated for investigation of the relationship between flaw inclination angle and cracking process, and relationship between specimen width and cracking process.